2016
DOI: 10.18632/oncotarget.11437
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA ANRIL is up-regulated in nasopharyngeal carcinoma and promotes the cancer progression via increasing proliferation, reprograming cell glucose metabolism and inducing side-population stem-like cancer cells

Abstract: Long noncoding RNAs play a vital role in diverse biological processes such as embryonic development, cell growth, and tumorigenesis. In this study, we report that LncRNA ANRIL, which encodes a 3834-nt RNA that contains 19 exons at the antisense orientation of the INK4B-ARF-INK4A gene cluster, generally up-regulated in nasopharyngeal carcinoma [1]. In a cohort of 88 NPC patients, ANRIL was highly expressed in advanced-stage cancer. Multivariate analyses revealed that ANRIL expression could serve as an independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 48 publications
3
99
1
Order By: Relevance
“…It was reported that ANRIL silencing repressed the proliferation of NPC cells. 16 In our study, the results of MTT assay also revealed that ANRIL knockdown led to the proliferation inhibition of NPC cells ( Fig. 3C and 3D).…”
Section: Anril Knockdown Inhibits Proliferation Of Npc Cellssupporting
confidence: 71%
See 1 more Smart Citation
“…It was reported that ANRIL silencing repressed the proliferation of NPC cells. 16 In our study, the results of MTT assay also revealed that ANRIL knockdown led to the proliferation inhibition of NPC cells ( Fig. 3C and 3D).…”
Section: Anril Knockdown Inhibits Proliferation Of Npc Cellssupporting
confidence: 71%
“…[13][14][15] Moreover, a recent study demonstrated that ANRIL was overexpressed in NPC cell lines and NPC tissues and promoted NPC progression through improving cell proliferation, reprograming cell glucose metabolism and inducing side-population stem-like cancer cells. 16 Growing evidence suggests that ANRIL functions as a fatal oncogene in many cancers, however, limited knowledge is available concerning whether lncRNA ANRIL affects the radiosensitivity of NPC.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA ANRIL, which encodes a 3834-nt RNA that contains 19 exons at the antisense orientation of the INK4B-ARF-INK4A gene cluster, could promote NPC progression by increasing cell proliferation and transformation, reprogramming cell glucose metabolism, and inducing side-population stem-like cancer cells. This may partially account for ANRIL-induced stem-like NPC cells and tumorigenesis [73]. In addition, knockdown of ANRIL repressed tumorigenicity and enhanced DDP-induced cytotoxicity through regulating microRNA let-7a in NPC cells, this provided a promising therapeutic strategy for NPC patients [54].…”
Section: Oncogenic Lncrnasmentioning
confidence: 99%
“…LncRNAs plays crucial roles on several systems and might be critical to various types of known cancer genes [8, 10-12]. It has been reported that lncRNAs function as important regulator in NPC.…”
Section: Introductionmentioning
confidence: 99%